Peran Partai Politik Sebagai Penyokong Pilpres Perspektif Fiqh Siyasah - Salsabila; Tamimi, Ajrina; Hasanah, Uswatun; Indra Putri, Septia Melati; Maylafaiza, Hawwin (Tabayyun : Journal Of Islamic Studies, 2023)
Political parties are a bridge that connects people's hearts and minds, and people's  demands are accommodated in political parties. That is the existence of political parties in Indonesia, especially those that support presidential elections from a sharia perspective. The question in this case is how to understand the role of political parties in realizing democratic post-conflict local elections and what their views are on achieving democratic post-conflict local elections. Which discusses the role of political parties in supporting presidential elections from a political-legal perspective. The data collected regarding the history of political parties comes from books that use historical theoretical analysis to discuss political parties to date. The research results show that political parties are a bridge to communicate dissatisfaction in social life. According to Law Number 10 of 2008 and Decree Number 2 of 2008, the aim of political parties is to realize the national ideals of the Indonesian nation, as regulated in the State Constitution. Republic of Indonesia in 1945. Political parties in Indonesia have an important role in the functioning of democracy because they are part of society and are the means and means of society in conveying their aspirations and ideas for the realization of democratic values in national life. and stated within the framework of Bhinneka Tunggal Ika, all these letters are in line with the verses of the Koran and Hadith which are the source of siyasah fiqh law.